Okja - Bong, Jun ho 1969- (The Criterion Collection, 2022)
"Master genre exploder Bong Joon Ho swirls pathos, dark satire, action, and horror into an exhilarating twenty-first-century fairy tale. An all-star cast including Tilda Swinton, Paul Dano, Steven Yeun, and Jake Gyllenhaal is led by An Seo Hyun as Mija, a South Korean girl growing up on an Edenic mountainside with her grandfather and best friend: Okja, a giant, empathetic "superpig" created as part of a secret GMO experiment. When Okja is abruptly torn away from her, Mija embarks on a perilous rescue mission that places her at the center of a sinister corporate conspiracy. While Bong’s trademark virtuosic set pieces dazzle, Okja’s beating heart is the connection between a girl and her superpig, made all the more poignant by the brilliant special effects that bring its animal star to unforgettable life." [criterion.com]
Original: Südkorea, USA 2017
Director-approved Blu-ray special edition features: 4K digital master, approved by director Bong Joon Ho, with Dolby Atmos sound ; new conversation between Bong and producer Dooho Choi ; new interviews with actors An Seo Hyun and Byun Heebong ; new interviews with members of the crew about the film’s cinematography, visual effects, and costume and production design ; short programs including a director’s video diary, featuring Bong; actors Paul Dano, Jake Gyllenhaal, Tilda Swinton, and Steven Yeun; and others ; teaser, trailer, and web promos ; English subtitle translation and English subtitles for the deaf and hard of hearing ; plus: An essay by critic Karen Han
Bildformat 2.39:1
Keywords: Film; Blu-Ray-Disc